Effect of Installation Platform on Bearing Capacity of an Offshore Monopile Foundation - Fabo, Chen; Ben, He; Peng, Gao; Xiangming, Ge; Yong, Zhou; Weijiang, Chu (Frontiers in Physics, 2022)
The installation platform will disturb the natural seabed adjacent to the monopile and consequently affect the monopile foundation's bearing capacity. Thus, the consideration of the influence of the installation disturbance is required in the monopile design, which can also save a fraction of the construction costs and avoid the security risks. It was found in a sensitivity analysis depending on the numerical simulations for an offshore monopile foundation installed using an installation platform, that the bearing capacities of the monopile were reduced by the penetration and extraction of the support legs of the installation platform, which were, a reduction about 7% of the horizontal bearing capacity of the monopile (decreasing with a larger diameter of the monopile), about 2% of the ultimate bending moment and almost no reduction of the vertical bearing capacity. For the monopile specifically subjected to the combined loads, it was found in SLS that the horizontal displacement and the rotation at the mudline increased about 5.13% and 2.12%, respectively, and the internal forces increased about 3.29%~9.87%; and the horizontal displacement and the rotation at the mudline increased about 4.56% and 2.79% in ULS, respectively, and the internal forces increased about 3.49%~7.79% in ULS. The study on the effects of the disturbance of the installation platform can be an important suggestion for the engineer in monopile design.